2019
DOI: 10.1063/1.5083052
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence in three dimensional magnetohydrodynamic plasma

Abstract: We report on a numerical observation of recurrence phenomenon in a three dimensional magnetohydrodynamic (MHD) plasma for certain classes of initial flow profiles. Our simulations discover such a behaviour for an initial Taylor-Green (TG) type of flow whereas under identical conditions an initial Arnold-Beltrami-Childress (ABC) flow fails to show recurrent behaviour. This difference in the dynamical behaviours is traced to the nature of the Rayleigh quotient in each case. The Rayleigh quotient which is an appr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However the investigation of the role of cross-helicity (also called Yoshizawa effect) on YM flow and others, in the context of various dynamo action is beyond the scope of the present work and will be addressed in future communication. The effect of fluid helicity injection in the context of recurrence [39] and quasi-recurrence [40] phenomenon is also an interesting study to investigate out, that will also be reported soon. The role of hydrodynamically unstable shear flow [41] at the largest scale is interesting to investigate in this context.…”
Section: Discussionmentioning
confidence: 99%
“…However the investigation of the role of cross-helicity (also called Yoshizawa effect) on YM flow and others, in the context of various dynamo action is beyond the scope of the present work and will be addressed in future communication. The effect of fluid helicity injection in the context of recurrence [39] and quasi-recurrence [40] phenomenon is also an interesting study to investigate out, that will also be reported soon. The role of hydrodynamically unstable shear flow [41] at the largest scale is interesting to investigate in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The three dimensional kinetic dynamo effect is matched with Galloway et al [11] in the case of ABC flow for a grid resolution of 64 3 . More benchmarking details and specifications about the code are given in earlier papers [12][13][14].…”
Section: Details Of Mhd3d Codementioning
confidence: 99%